Changing Trends of Maternal Mortality in a Rural Medical College in Eastern India: A 23-Year Retrospective Study - Debjani Deb; Anindya Kumar Das; BC Kameswari; Aditya Prasad Sarkar (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Maternal mortality in a region is a measure of reproductive health of women in that area. The direct causes of maternal deaths are largely preventable. A new era of more comprehensive, international development agenda-the Sustainable Development Goals (SDG 3.1) was launched by the United Nations General Assembly 2015, New York for ending preventable maternal deaths. Aim: To determine the causes and changing trends of maternal mortality in at a rural centre in Eastern India. Materials and Methods: A retrospective observational study was carried out in the Department of Obstetrics and Gynaecology of Bankura Sammilani Medical College in West Bengal in Eastern India. Individual hospital records of all the maternal deaths, from January 1998 to December 2020 were collected. Data regarding demographic profile and reproductive parameters like gravida, parity, antenatal care and cause of death were collected. The records were divided into two four yearly periods, to compare the changing trends (1998-2001) vs (2017-2020) and three five yearly (2002-2006), (2007-2011), (2012-2016) periods. The first term (1998-2001) was taken as the reference period. Results: Comparison between first (1998-2001) and last term (2017-2020) shows significant declining trend of Maternal Mortality Ratio (MMR) (364 vs 148)/100000 live birth (p-value <0.00001). Majority of deaths occurred in primigravida (57.5% vs 60.6%). Direct obstetric causes accounted for majority of the deaths, but with a declining trend (74.7% vs 66.9%). Eclampsia remained the leading direct cause (35.5% vs 32.2%) followed by haemorrhage (20.4% vs 18.8%) and sepsis (18.8% vs 15.7%) in the first term (1998-2001) vs last term (2017-2020). Jaundice 6.45% vs 10.3%, heart disease 2.15% vs 7.1%, embolism 4.3% vs 0.8%, anaemia 6.45% vs 1.6% and other diseases 5.91% vs 13.4% in the first vs last term were the indirect causes of maternal mortality. Conclusion: There is a declining trend of maternal mortality since 1998, which can be attributed to improvement at all levels of healthcare. Eclampsia/preeclampsia and its complications remain the leading cause of maternal mortality. Majority of these maternal deaths can be prevented by regular screening of highrisk cases, integrated antenatal and postnatal care, institutional deliveries, timely referral, and proper implementation of national health programmes.